Exploring self-care within the context of cognitive behavioural therapy and supervision - Prasko, Jan; Abeltina, Marija; Gecaite-Stonciene, Julija; Burkauskas, Julius; Krone, Ilona; Jurisova, Erika; Zatkova, Marta; Vanek, Jakub; Slepecky, Milos; Ociskova, Marie (Neuro-endocrinology letters, 2024)
This article emphasizes the critical role of self-care in the professional lives of cognitive behavioural therapy (CBT) therapists and supervisors. It delves into the importance of self-care, elucidating its significance in maintaining therapists' mental health and effectiveness. The article presents a range of practical strategies that promote self-care, providing therapists and supervisors with specific steps to incorporate self-care into their daily routines. Moreover, the article explores common challenges and barriers to self-care, such as a lack of time, feelings of guilt associated with prioritizing one's needs, and a lack of available resources for self-care. The article aims to deepen our understanding of the complexities of practising self-care by shedding light on possible obstacles. In addition, the article includes case vignettes that demonstrate tangible examples of the positive impact of self-care on therapists' mental health and effectiveness. The overarching goal of this article is to encourage ongoing discussion and research on self-care. It advocates a greater emphasis on self-care in CBT and CBT supervision (CBTS), intending to promote the health and well-being of those who dedicate their lives to caring for others. The insights and strategies presented in this article serve as a resource for therapists and supervisors striving to achieve a balanced lifestyle while effectively catering to the needs of their clients.
Keywords: kognitivně behaviorální terapie; Self Care; emoce; Emotions; duševní zdraví; lidé; péče o sebe; Mental Health; Cognitive Behavioral Therapy; Humans